Risk assessment associated with natalizumab treatment. Issue 2 (12th March 2012) - Alcobia, A.; Leandro, A.; Santos, P.
Abstract : Background: Progressive multifocal leukoencephalopathy (PML) is an opportunistic viral infection of the central nervous system that usually leads to death or severe disability. In patients receiving natalizumab treatment, some independent risk factors are associated with an increased risk of PML: duration of treatment (especially beyond 2 years), the use of immunosuppressive agents (eg, mitoxantrone) before receiving the drug and the presence of antibodies to JCV. Purpose: To calculate the estimated risk of developing PML in patients being treated with natalizumab in Garcia de Orta Hospital. Materials and methods: A literature search was performed to determine the relative risk of developing PML for the different factors being assessed. Patients with multiple sclerosis on natalizumab treatment in June 2011 were evaluated regarding the risk of developing PML. Results: This evaluation included 13 patients with multiple sclerosis on natalizumab treatment, 10 of whom were females (76.9%), with a mean age of 37.0±4.5 years (18-56 years). Five patients (38.5%) had been treated with natalizumab for over two years, three (23.1%) had been taking immunosuppressive agents prior to natalizumab and seven (53.8%) had a positive result for JCV antibodies. Regarding the risk of PML, 4 patients had no risk factors (PML risk=0.19‰), 5 patients had only one risk factor (PML risk=1.37‰), 2 patients accumulated 2 risk factors (PML risk=4.3‰) and 2 patients had all three risk factors in analysis (PML risk=7.8‰). The presence of the 3 risk factors increases the risk of PML by 41 times in MS patients treated with natalizumab when compared with an absence of risk factors. Conclusions: This analysis helped determine which patients had an increased risk of developing PML, allowing the Neurology department to assess the risk-benefit of natalizumab treatment more objectively.